Philosophical Approaches in Religious Thought: A Systematic Literature Review - Septemi, Yulia; Sari, Ice Linsa; Yadi, Supri; Helita, Helita; Elesti, Yesmi (PPSDP International Journal of Education, 2025)
This systematic literature review analyzes the interplay between philosophical approaches and religious thought. By reviewing 15 relevant journal articles, this study explores how philosophy and religion, despite differing truth criteria (revelation vs. reason), can be complementary in the search for life’s meaning. The analysis focuses on key thinkers such as Thomas Aquinas, Al-Ghazali, and Muhammad Iqbal, highlighting perennial philosophy as a bridge for interfaith dialogue and pluralism. The study concludes that the integration of science and religion is not only possible but essential for a holistic understanding of human existence and the promotion of global well-being. This integration enriches both intellectual and spiritual dimensions of life. The findings argue against a rigid separation between scientific, philosophical, and religious education. It implies that a holistic education system should integrate these disciplines to provide students with a more complete worldview. The study’s primary contribution is its clear and argued conclusion that a fragmented view of reality (where science, philosophy, and religion are separate) is insufficient. It makes a compelling case that a holistic understanding, which integrates these domains, is necessary for a complete picture of human existence.